2003
DOI: 10.21608/ejabf.2003.1805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Euphorbia Peplus Plant Extract and the Antihelmenthic Prazequantel on the Defence System of Biomphalaria Alexandria Snail

Abstract: T he effect of sublethal concentrations of£ pephis water suspension and praziquantel water solution on the defense system of Biomphalaria cdexandrina was examined by laboratory experiments.The mean number of haemocytes decreased insignificantly after the first week of snail exposure to the plant extract-Thereafter, a significant increase occurred after the second week of exposure. Treatment with praziquantel showed a significant increase in haemocytes after the 3 rd and 4 lh weeks of exposure. Haemocytosis rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…Snails exposed to LC25 of Bestacid E.C insecticide then to either the same concentration or double concentration of the ethanolic extract of O. basilicum plant caused a highly significant increase in the mean total number of hemocytes (p˂ 0.001) than that for control group. These results coincide with Helal et al (2003) who observed significant increase in B. alexandrina hemocytes after exposure to the water extract of the plant Euphorbia peplus. Higher numbers of circulating hemocytes could be due to release of hemocytes from tissue depots as they participate in tissue repair (Nelson et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Snails exposed to LC25 of Bestacid E.C insecticide then to either the same concentration or double concentration of the ethanolic extract of O. basilicum plant caused a highly significant increase in the mean total number of hemocytes (p˂ 0.001) than that for control group. These results coincide with Helal et al (2003) who observed significant increase in B. alexandrina hemocytes after exposure to the water extract of the plant Euphorbia peplus. Higher numbers of circulating hemocytes could be due to release of hemocytes from tissue depots as they participate in tissue repair (Nelson et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in hemcytes may be considered as a haemolysis response to the multiple pollution in Lake Burullus. This was mentioned by (Helal et al, 2003) that hemocytosis represents a response to external stress or certain stimuli and may originate from a variety of biotic or abiotic sources (Wolmarans & Yssel 1988). These results were in agreement with (El-Kayat et al, 2015a) who found that the snails collected from ElManzala Lake showed decrease in hemolcytes.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile blood of native fish samples collected from El-Hamoul and Sidi-Salem sites showed highly significant increase of WBCs count, this increase could be due to their function as they are defensive in nature also, leukocytosis is directly proportional to the severity of damage and stress which as a consequence result in the stimulation of immunological defense, (Javed and Usmani 2012). The increase in small and large granulocytes of snail hemolymph and in WBCs of fish was suggested to indicate alteration in defense mechanism against the action of heavy metals toxicity bio-accumulated in snail and fish tissues as previously reported by Zaghloul (2001), (Helal et al, 2003) and Zaghloul et al (2005). Mottobus native fish samples showed the highest Hb level (% of change was 18 in comparison to control) and in spite of non-native Mottobos showed reduction in Hb than control (-27%) it represented also, the highest level among other non-native exposed samples, this is side by side with the present results showing that Mottobus site had the least levels in most of water quality creiteria and its samples showed the least bioaccumulation confiming the more healthy lake ecosystem in Mottobus.…”
Section: Discussionsupporting
confidence: 69%
“…Being small cells with a large nucleus, they are thought to be the progenitors of the other populations [11,17] . Regarding B. alexandrina snails, previous research studied their hemocytes [18][19][20][21] , yet, information about the functional attributes of their populations and subpopulations in response to S. mansoni infection is still deficient.…”
Section: Introductionmentioning
confidence: 99%